Tracing the veins : of copper, culture, and community from Butte to Chuquicamata - Finn, Janet L., 1956- (Berkeley : University of California Press, 1998)
This tale of two cities - Butte, Montana, and Chuquicamata, Chile - traces the relationship of capitalism and community across cultural, national, and geographic boundaries. Combining social history with ethnography, Janet Finn shows how the development of copper mining set in motion parallel processes involving distinctive constructions of community, class, and gender in the two widely separated but intimately related sites.
Front matter -- Contents -- Illustrations -- Preface -- ONE. Tracing the Veins -- TWO. Mining History A Political Chronology -- THREE. Mining Community -- FOUR. Mining Men and Designing Women -- SIX. Miner's Consumption -- SEVEN. Trust, Betrayal, and Transformation -- EIGHT. Food for Thought and Action -- APPENDIX I. Copper Production, 1920-1972 -- APPENDIX 2. Copper Production, 1934-1972 -- Notes -- Bibliography -- Index
Includes bibliographical references (pages 277-295) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Anaconda Company; Anaconda Company; Copper industry and trade -- Social aspects -- Montana -- Butte; Copper industry and trade -- Social aspects -- Chile -- Chuquicamata; Cuivre -- Industrie -- Aspect social -- Montana -- Butte; Cuivre -- Industrie -- Aspect social -- Chili -- Chuquicamata; BUSINESS & ECONOMICS -- Industries -- General; SOCIAL SCIENCE / Anthropology / Cultural & Social; Copper industry and trade -- Social aspects; Chile -- Chuquicamata; Montana -- Butte; Industries; Business & Economics; anaconda company; anthropology; betrayal; business; butte; capitalism; chile; chuquicamata; class; community studies; community; consumption; copper mining; copper production; cultural boundaries; danger; ethnography; gender; geographic boundaries; global capitalism; local culture; miners; mining community; mining history; mining life; mining men; mining; montana; national boundaries; politics; privation; privilege; silicosis; social history; transformation; wasting